Metabolism and effects on platelet function of the purified eicosapentaenoic and docosahexaenoic acids in humans. - von Schacky, C (1985)
Metabolism and effects on platelet function of 6 g/d for 6 d of either eicosapentaenoic acid (EPA, C20:5 omega-3) or docosahexaenoic acid (DCHA, C22:6 omega-3) in volunteers were compared in a randomized crossover study. Incorporation kinetics revealed that EPA appeared in plasma free fatty acids and plasma phospholipids after 4 h, but was not incorporated into platelet phosphatidylcholine and -ethanolamine until day 6. This indicates that platelet fatty acid composition does not immediately reflect that of the surrounding plasma milieu, but rather may be determined during megakaryocyte maturation. Importantly, EPA was not incorporated into platelet phosphatidylinositol or -serine in vivo, thus reflecting selective biosynthesis of platelet phospholipids. After dietary EPA, C22:5 omega-3 increased in plasma and platelet phospholipids. In contrast, DCHA-levels were unaltered. After DCHA-ingestion, C20:5 omega-3 concentrations rose in plasma phospholipids, implying that retroconversion took place. These findings indicate that dietary DCHA can serve as a source of EPA. During this short-term study, ingestion of both EPA and DCHA resulted in reduced platelet aggregation in response to collagen. The response to ADP was lowered significantly only by DCHA. After either EPA or DCHA, thromboxane formation was unchanged in serum derived from clotted whole blood as was total in vivo synthesis measured by excretion of immunoreactive 2,3-dinor thromboxane B2/3. We conclude that DCHA reduces platelet responsiveness, contributing to the antithrombotic effects of omega-3 fatty acid-rich fish oil ingestion, of which DCHA is a major component.